Conflitos socioambientais no parque estadual de Terra Ronca – GO : desafios para o desenvolvimento do turismo comunitário - (:unkn) unknown (Universidade Estadual de Goiás, 2018)
This research is associated with the research line 'Analysis of biodiversity in natural and anthropogenic landscapes' of the Sensu Strict Postgraduate Program in Environment and Society, at the MSc Academic level, State University of Goiás. It is funded by the University itself, as a scholarship, by the public notice 009/2017/CCB. This dissertation meets the assumption is that territorial and ecological relations are burdened by socio-environmental conflicts between social actors and that these same conflicts directly affect the development of Community Tourism. Considering this perspective, the general objective of the research is to carry out an interdisciplinary examination of the complex relationships inherent to the socioenvironmental conflicts in the State Park of Terra Ronca, under the bias of Political Ecology and Community Tourism, linked to environmental dynamics, economy, politics, culture and tourism. The methodological course adopted follows procedures of collection and analysis of exploratory approach in the collection of bibliographical, documentary and human data through focal informants. The territory where the research takes place is in the northeast of the State of Goiás, in the municipality of São Domingos, tourist region of the Waters and Caves of the Cerrado. In this one the research of cabinet was realized and a work of field, in order to approach of the researcher with the studied object. The study of the office contemplated the formation of the theoretical contextualization that underlies the subjects addressed (Conflicts, Socio-environmental Conflicts, Political Ecology and Community Tourism). An interpretative reading was also made of the legal instruments that govern the Park and the elements that occupy the territory of São Domingos-GO. It ends with the identification of socio-environmental conflicts based on the discourse of the social actors involved in the territory.
Keywords: Conflitos Socioambientais; Unidades de conservação; Povos e comunidades tradicionais; Ecologia política; Turismo comunitário; Socio-environmental Conflicts; Conservation Units; Peoples and Traditional Communities; Political ecology; Community tourism; OUTROS; CIENCIAS SOCIAIS APLICADAS::TURISMO